Exploring the Relationship between Functional Movement, Skill-related Physical Fitness, Skill Performance, Competitive Anxiety, and Sport-confidence in College Footballers - Dojin An; Namsu Kim (Asian Society of Kinesiology, 2023)
OBJECTIVES The purpose of this study was to explore the relationship among functional movement, skillrelated physical fitness, skill performance, competitive anxiety, and sport-confidence in college footballers. METHODS In this study, 76 college footballers were selected as research participants to investigate their body composition factors and general characteristics, and their functional movement, quickness, speed, agility, dribbling, competitive anxiety, and sport-confidence were measured. For analysis of study results, descriptive statistics, and Pearson's product-moment coefficients of correlation were used. And then, multiple and simple linear regression were conducted to verify the influence of psychological, functional movement, skill-related physical fitness, and skill performance factors. RESULTS As a results of the analysis, correlation between functional movement factors, cognitive anxiety, somatic anxiety, and state sport-confidence were significant considerably. In addition, deep squat, rotary stability, and shoulder mobility among the FMS sub-factors were found to have a significant effect on cognitive anxiety, somatic anxiety, state sport-confidence, and trait sport-confidence. Also, dribbling factor was found to have a significant effect on cognitive anxiety. CONCLUSIONS Functional movement and dribbling factors are related to competitive anxiety and sportconfidence of college footballers. follow-up studies are needed to verify the mechanism of the relationship between physical, skill-related physical fitness, skills, and psychological factors.